Once is not enough: withholding postoperative prophylactic antibiotics in prosthetic breast reconstruction is associated with an increased risk of infection - Clayton, John L; Bazakas, Andrea; Lee, Clara N; Hultman, C Scott; Halvorson, Eric G (Plastic and reconstructive surgery (1963), 2012)
There has been a trend toward limiting perioperative prophylactic antibiotics, based on research not conducted in plastic surgery patients. The authors' university hospital instituted antibiotic prescribing guidelines based on the Surgical Care Improvement Project. An increased rate of surgical-site infections was noted in breast reconstruction patients. The authors sought to determine whether the change in antibiotic prophylaxis regimen affected rates of surgical-site infections. A retrospective study compared patients undergoing breast reconstruction who received preoperative and postoperative prophylactic antibiotics with a group who received only a single dose of preoperative antibiotic. Type of reconstruction and known risk factors for implant infection were noted. Two hundred fifty patients were included: 116 in the pre-Surgical Care Improvement Project group and 134 in the Surgical Care Improvement Project group. The overall rate of surgical-site infections increased from 18.1 percent to 34.3 percent (p = 0.004). Infections requiring reoperation increased from 4.3 percent to 16.4 percent (p = 0.002). Multivariate logistic regression demonstrated that patients in the Surgical Care Improvement group were 4.74 times more likely to develop a surgical-site infection requiring reoperation (95 percent CI, 1.69 to 13.80). Obesity, history of radiation therapy, and reconstruction with tissue expanders were associated with increased rates of surgical-site infection requiring reoperation. Withholding postoperative prophylactic antibiotics in prosthetic breast reconstruction is associated with an increased risk of surgical-site infection, reoperation, and thus reconstructive failure. The optimal duration of postoperative prophylactic antibiotic use is the subject of future study.